Axiological Review of the Philosophy of Defense Science in Efforts to Improve National Defense Capabilities - Martadinata, Ilham; Gibran, Muhamad Noor; Kaunang, Elfira Sylviani; Hadianto, Muhammad; Risman, Helda (Jurnal Multidisiplin Madani, 2024)
The purpose of this study is to ascertain how defense science philosophy fits into efforts to strengthen the nation’s fundamental defense capabilities. With the researcher serving as the primary research instrument and a descriptive and explanatory design approach, the research employs a descriptive qualitative methodology. With this method, a literature evaluation of the research that has been done is used to obtain more precise and in-depth information, some of which is gained later on by the researchers. Only by studying the philosophy of defense science using a succinct approach to outline the philosophy of defense science will it be possible to improve national defense capabilities through the application of an in-depth understanding that is critical, systematic, methodological, and fundamental. The emergence of the globalization, science, and technology eras can be advantageous to a nation, but they can also be dangerous for its security and defense. particularly about the state’s necessity to fulfill its national objectives, where security can only be attained via defense. Stated differently, defense is an essential human urge that cannot be suppressed. The fundamental idea behind this acknowledgment is that everyone and every person has a duty and responsibility to take part in defending their nation, which includes working to instill a strong sense of nationalism, patriotism, and fighting spirit in the Indonesian state